The Comparison of Online Counseling Researches in Turkey and USA - Amanvermez, Yagmur (ELSEVIER SCIENCE BV, 2015)
This research aims to investigate studies about online counseling both in Turkey and USA. It is designed as a case study and for the analysis of the data content analysis is used. Six studies on online counseling in Turkey are investigated within the scope of this study. Also six studies from the USA are investigated from EBSCOhost database, between the years of 2010 and 2014. Results indicate that researches about online counseling in the USA are more prone to investigate the effectiveness of this kind of distant helping than the studies which conducted in Turkey. In addition, researches in the USA are focused on counseling process and outcome, namely, therapeutic alliance, client satisfaction with online help, whether symptoms are reduced after the online treatment. Results also indicate that experimental research strategies are applied mostly in the researches about online counseling in the USA. On the other hand in Turkey, researches have just began about using information and communication technologies (ICT) in counseling and there is no experimental study about online counseling. Most of the studies in Turkey are related with clients' and counselors' views or perceptions about online counseling. All researches are designed as a descriptive model. In conclusion, researches in Turkey are needed to be developed and diversified by the researchers. In this context, it is thought that the comparison of the online counseling between researches in Turkey and the USA is crucial for the development of this field. (C) 2015 Published by Elsevier Ltd.
Keywords: Online counseling; online counseling in Turkey; online counseling in USA; comparison; Education & Educational Research; Social Sciences - Other Topics